2000
DOI: 10.1530/eje.0.1420224
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid structure and size and two-year follow-up of solitary cold thyroid nodules in an unselected population with borderline iodine deficiency

Abstract: Objective: Multinodular goitre has been found with a high prevalence in iodine-deficient areas, but less frequently in iodine-replete areas; the iodine intake sufficient to prevent goitre has not been established, however. Methods: We report data from an ultrasonic investigation of the thyroid glands of 2656 randomly selected subjects aged 41 to 71 years in an area with borderline iodine deficiency. Results: Median iodine concentration in spot urine samples was 70 mg/l. Multinodular thyroid structure was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 30 publications
5
61
1
5
Order By: Relevance
“…Previous investigators found an increased risk for developing a goiter due to elevated SCN 2 concentrations of 8 -12 mg/l (normal 2 -4 mg/l) in the serum of smokers in comparison to nicotine abstinence (11,36,37 (10,11,35,37). Surprisingly, in contrast to SCN 2 excretion, the urinary I 2 excretion of our probands did not correlate with thyroid volume, because the prevalence of goiter increases with age (3,29,34). The small mean thyroid volume in our probands, especially in young male probands with moderate to severe I 2 deficiency, most likely prevented an inverse correlation between urinary I 2 and thyroid volume.…”
Section: Correlations Between Urinary Icontrasting
confidence: 72%
See 1 more Smart Citation
“…Previous investigators found an increased risk for developing a goiter due to elevated SCN 2 concentrations of 8 -12 mg/l (normal 2 -4 mg/l) in the serum of smokers in comparison to nicotine abstinence (11,36,37 (10,11,35,37). Surprisingly, in contrast to SCN 2 excretion, the urinary I 2 excretion of our probands did not correlate with thyroid volume, because the prevalence of goiter increases with age (3,29,34). The small mean thyroid volume in our probands, especially in young male probands with moderate to severe I 2 deficiency, most likely prevented an inverse correlation between urinary I 2 and thyroid volume.…”
Section: Correlations Between Urinary Icontrasting
confidence: 72%
“…In our study smokers had a tendency towards higher values for thyroid volume in comparison to non-smokers, without reaching statistical significance (Table 3). Because prevalence of goiter increases with age and decreases with increased I 2 intake (3,29,34,35), the younger mean age of our population as well as the elimination of severe I 2 deficiency in Saxony (14) may obscure to the (insignificant) difference between smokers and non-smokers. We are aware that the 30% non-response regarding smoking behaviour could cause some selection bias.…”
Section: Correlations Between Urinary Imentioning
confidence: 98%
“…Larger Tvol has been found in areas with both iodine deficiency (38)(39)(40)(41)(42) and iodine excess (28,29,43) . Iodine-induced goitre due to iodine-rich drinking water has been found in China (43) .…”
Section: Thyroid Volumementioning
confidence: 99%
“…The nodular goitre shows regional variations in the society but it varies between 4% and 7%. This ratio reaches up to 23% in men and 46% in women in proportion to age 13,14 . The nodular hyperplasia diagnosis of 272 (52.2%) of 521 cases were taken in our study and 211 of them were women and 61 of them were men.…”
Section: Resultsmentioning
confidence: 96%